Metastasis to the gastrostomy site in a patient with pharynx cancer after percutaneous endoscopic gastrostomy: a case report. (2nd August 2020) - Vujasinovic, Miroslav; Öst, Åke; Bark, Rusana; Brismar, Torkel; Hynning, Boel; Lindblad, Mats; Elbe, Peter
Abstract: A stenosing tumour in the throat region is a common indication for percutaneous endoscopic gastrostomy (PEG), which may be used for enteral nutrition in palliative cases or placed prior to curative treatment (surgery, radiotherapy and/or chemotherapy) and removed when the patient has recovered and has a reliable and adequate oral intake. Major complications related to PEG are rare, but their treatment poses a challenge. We are presenting a case of the transmission of metastasis to the gastrostomy site in a patient with pharynx cancer after percutaneous endoscopic gastrostomy.